Modelling the financial performance of large cooperatives in National Capital Region, Philippines, thru capital structure optimization - Parone, Fe Argente (Animo Repository, 2023)
Cooperatives constitute groups of individuals known as members who unite with a shared objective and formally register with government regulatory bodies to engage in economic activities benefiting both themselves and their community. Despite the positive impact cooperatives have on people’s lives, their relatively small size has resulted in limited recognition in terms of community patronage, financial support, academic attention, and government backing. Consequently, these organizations have remained underrepresented in academic research. For this reason, the researcher, being employed by the largest cooperative in the Philippines, is intrigued by the financial performance of this sector in relation to its capital structure. Numerous research endeavors have been undertaken to explore the relationship between capital structure and the financial performance of various types across global business entities. The researcher would like to find out if the proven relationship holds true for the 24 large-type multipurpose and credit cooperatives in the National Capital Region of the Philippines. Should such a relationship exist, the objective is to develop a model that would maximize financial performance through an optimal capital structure. The study employs various regression analyses, including Pooled OLS, Fixed Effects, and Random effects, to determine the fittest model. Return on Assets (ROA) and Return on Equity (ROE) serve as dependent variables, while Debt to Equity Ratio (DER), Debt to Asset Ratio(DA), Members Equity to Total Asset Ratio (META), and External Borrowings to Total Asset Ratio (EBTA) was used as measures of capital structure. The results showed that DER, DA, and META exert a statistically significant impact on ROE, whereas DA and META hold statistical significance on ROA. From the findings, the researcher recommends a financial model aimed at maximizing financial performance by generating funds through share capital contributions from the members. Moreover, the optimization of fund generation can be achieved through a financial technology platform applicable to all cooperatives, including those with limited automation in their processes and databases.